2016
DOI: 10.1097/mej.0000000000000208
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical knowledge and skill retention 4 months after a European Paediatric Life Support course

Abstract: According to our findings, theoretical knowledge of the EPLS course uniformly declines, irrespective of the provider characteristics, whereas retention of certain skills is evident 4 months after the course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…EPALS is designed for healthcare workers who are involved in the resuscitation of newborns, infants or children providing sufficient competences to manage critically ill or injured children during the first hour of illness. [215][216][217][218] Refresher training in paediatric basic life support and relief of foreign body airway obstruction is included.…”
Section: Specific Formats Of Erc Resuscitation Coursesmentioning
confidence: 99%
“…EPALS is designed for healthcare workers who are involved in the resuscitation of newborns, infants or children providing sufficient competences to manage critically ill or injured children during the first hour of illness. [215][216][217][218] Refresher training in paediatric basic life support and relief of foreign body airway obstruction is included.…”
Section: Specific Formats Of Erc Resuscitation Coursesmentioning
confidence: 99%
“…Multiple studies have demonstrated that the skills obtained during CPR training often decay as rapidly as within a few months. 15 This, in combination with infrequent exposure to cardiac arrest in pediatric patients in the ED, can severely diminish the quality of CPR. We found that EPs perform CPR on adults approximately 4 times a year and only once every 5 years in children.…”
Section: Discussionmentioning
confidence: 99%
“…Open access respiratory technology in RLS is the presence of a highquality training programme. 5 Current data suggest that knowledge and skills retention after initial training programmes decline over time, [6][7][8][9][10][11] highlighting the need for ongoing refresher training in order to sustain competency. As part of the initial deployment of high flow in the paediatric intensive care unit (PICU) at Instituto Nacional de Salud del Niño (INSN) in 2016, we developed a comprehensive multidisciplinary high flow training programme that included initial and refresher training sessions for all PICU staff.…”
Section: Introductionmentioning
confidence: 99%